AKTIVITAS ANTIOKSIDAN DAN KANDUNGAN SENYAWA FENOLAT BIJI JAMBLANG (Syzygium cumini (L.) Skeels) - Lia Marliani (JURNAL FARMASI GALENIKA, 2014)
Jamblang (Syzygium cumini (L.) Skeels) is one of local plantsfrom Indonesia that is rare cultivated. Some compounds contained in Jamblang is probably potential to have antioxidant activity. This study was conducted to determine the antioxidant activity and content of phenolic compounds of jamblang seeds. Extraction was done by reflux method using water solvent and dried by freeze drying method. Antioxidant activity was tested qualitatively and quantitatively by reduction of free radical 1-1-diphenyl-2 picrylhydrazyl (DPPH) method. Antioxidant activity was qualitatively testedby Thin Layer Chromatography using butanol-acetic acid-water (4: 1: 5) as mobile phase and 0.2% DPPH in metanol as spotting agent. Antioxidant activity was quantitatively measured by UV-visible spectrophotometry at Î» 516 nm and determined by the IC50 value. Vitamin C was used as comparison. The content of phenolic compounds analysis was done qualitatively and quantitatively. The Qualitative test was done by thin layer chromatography using butanol-acetic acid-water (4: 1: 5) as mobile phase and 10% FeCl3as spotting agent. Determination of total phenolic compound was using the Folin-Ciocalteu reagent and measured by UVvisible spectrophotometry at Î» 765 nm. The IC50 values of jamblang seed extract and vitamin C respectively were67.098 ppm and 6.98 ppm. Phenolic compound was suspected as active antioxidants compound. Total phenolic content of seed extractis 119.251 Â± 2.494 mg / g.